Regional population differentiation in the morphologically diverse, elevationally widespread Nearctic skipper Polites sabuleti - Joshua P. Jahner; Matthew L. Forister; Chris C. Nice; James A. Fordyce; Joseph S. Wilson; Dennis D. Murphy; Zachary H. Marion; Arthur M. Shapiro (Journal of Biogeography, 2015)
Aim To evaluate three phylogeographical models associated with the presence of mountains (montane vicariance, sky island and parapatry) as drivers of intraspecific diversification in the sandhill skipper, Polites sabuleti (Lepidoptera: Hesperiidae), a morphologically variable species found in a variety of habitats from sea level to the alpine zone. Location Western North America. Methods The mitochondrial cytochrome c oxidase subunit II region was sequenced in 189 P. sabuleti individuals. Mitochondrial sequences were used in a spatial analysis of molecular variance ( SAMOVA ) to evaluate geographical population structure. AFLP markers were also generated for 347 individuals in order to estimate admixture proportions and examine population differentiation based on the nuclear genome. Results Twenty‐five mitochondrial haplotypes and 42 anonymous AFLP loci were found across 36 collection localities. Mitochondrial variation suggests a degree of regional population structure, although at least one of the inferred population groups extends over nearly the entire geographical range of the species. Analyses of nuclear data ( AFLP s) identified five genetic clusters, including one restricted to high elevations in the Sierra Nevada. Main conclusions The distribution of genetic variation within Polites sabuleti , a species with a broad elevational range, does not strictly support either mountain‐associated vicariance or ‘sky island’ isolation as the dominant process. Instead, we find complex population structure, including evidence for divergence between high‐ and low‐elevation populations in the Sierra Nevada mountains.